Penentuan Konsentrasi Ammonium dalam Air Sungai Pelayaran Ngelom: Determination of Ammonium Concentration in Ngelom . Shipping River Water - Ngibad, Khoirul (Universitas Muhammadiyah Sidoarjo, 2019)
Ammonium (NH4+) is a form of ammonia (NH) compound in thewater at low pH. The ammonium can cause poisoning in aquatic life. The purpose of this study was to determine the ammonium concentration in the Ngelom river water sample that flows in the Ngelom village, Taman district, Sidoarjo Regency. The measurement of ammonium concentration in river water samples was carried out using the UV-Vis spectrophotometrymethod with Nessler reagent based on the Nessler reagent reaction (K2HgI4) with ammonium in a base solution which would form a colloidal yellow brown dispersion which absorbance measured at 410 nm. Ammonium absorbance is proportional to the ammonium concentration in the sample. The sampling technique in this study used purposive sampling. Samples were taken at 10 trial points, every 5 meters to the right and left from the center point (Ngelom's River bridge to Maarif Hasyim Latif University). Ammonium concentration was determined in the linear concentration range of 1 – 5 mg/L with a correlation coefficiency value (r) of 0.9615 with limit of detection and limit of quantitation of 0.105 mg/L and 0.352 mg/L, respectively. The results of testing the river water samples showed that the ammonium concentration in 10 samples of river water ranged from 1.61 – 14.68 mg/L. All of the sample was not eligible requirements of the Republic of Indonesia PP No. 82 of 2001 about Water Quality Management and Water Pollution Control.